Int. J. Adv. Res. Biol. Sci 2017
DOI: 10.22192/ijarbs.2017.04.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effect of Black Raspberry and Apricot Juice against Colon Cancer Induced by Azoxymethane in Male Rats

Abstract: This study was carried out to evaluate the anticancer effect of black raspberry juice (RJ) and apricot juice (AJ) against colon cancer induced by Azoxymethane (AOM) in rats and to examine the possible mechanisms. Forty two Sprague Dawley male rats were used and randomly distributed into 6 equal groups (n=7). The 1 st group was negative control and each rat from the other 5 groups was given a single subcutaneous dose (15 mg/kg b.wt.) of AOM once weekly for 2 weeks to induce colon cancer. The 2 nd group was kept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In the same context, Zhang et al (2011) (13) , Kresty et al (2016) (7) , and Ibrahim. (2017) (14) reported similar results in cervical cancer, esophageal cancer and colorectal cancer respectively. Moreover, decreasing the IC 50 value with increasing time of treatment from 24h to 72h time intervals indicates that the cytotoxic effect of BR against OSCC cell line could be efficiently exerted with the same efficacy either by a high dose of BR for limited time, or reduced BR dose for prolonged time.…”
Section: Discussionmentioning
confidence: 53%
“…In the same context, Zhang et al (2011) (13) , Kresty et al (2016) (7) , and Ibrahim. (2017) (14) reported similar results in cervical cancer, esophageal cancer and colorectal cancer respectively. Moreover, decreasing the IC 50 value with increasing time of treatment from 24h to 72h time intervals indicates that the cytotoxic effect of BR against OSCC cell line could be efficiently exerted with the same efficacy either by a high dose of BR for limited time, or reduced BR dose for prolonged time.…”
Section: Discussionmentioning
confidence: 53%
“…found that amygdalin reduced tumor cell proliferation in prostate and bladder cancer cells, causing a considrable cell cycle regression [8,9]. Ibrahim et al, (2017) found that the apricot juice has an anticancer effect against colon cancer by reducing colon cancer biomarkers TNF-α, NF-κB, IL-1β and IL6 levels in the serum [10]. Arshi et al, (2019) observed that the amygdalin decreased growth and proliferation of stomach cancer (AGS), lung cancer (A549) and breast cancer (MCF7) through down-regulating the expression level of two antiapoptotic genes [11].…”
Section: Introductionmentioning
confidence: 99%